Response Of A Medicinal Plant Peganum Harmala To Iron Oxide Nanoparticles F3O4(Nps) (Journal of Pharmaceutical Negative Results, 2022)
Iron nanomaterials are widely present in the environment and their concentrations are increasing day by day. In many applications, iron nanomaterials are included, but the minimum and maximum concentrations that are not harmful to plants are not yet known. Effect of F3O4(NPs) on Peganum harmala plants for the purpose of showing anatomical responses as effective biomarkers for increasing the concentration of nanomaterials in the ecosystem. Electron microscopy to determine the effect of different doses of F3O4(NPs) ranging from (0-600 mg / L) were used. The cross-sections of leaves were compared in terms of epidermis, parenchyma cells, vascular cylinder, especially xylem and phloem vessels. Epidermal variations were studied stomata, guard cells and normal cells of the epidermis. The laboratories of the Department of Environmental Sciences and Pollution at the College of Science, University of Kufa for the year 2022 were used to conduct experiments. The anatomical results of the studied plants showed that the largest effect was on the epidermis of the plants, especially on the stomata system, where the stomata were closed and decreased in number, while the vascular system was less affected by the variation in the concentration of F3O4(NPs) compared to the rest anatomical indicators. The severity effect was proportional to the increase in concentration. The results indicate that an insufficient supply of F3O4(NPs) (150 mg / L) can be a plant growth stimulator and the results can be used in practical applications to increase production and improve crops as a fertilizer. Whereas, treatments with high concentrations inhibit antioxidants, causing a deficiency of growth activity in plants.